Swimming Health Monitoring System with Heartbeat and Oxygen Sensor - Azman, Husna Madiha; Omar, Rosli (Evolution in Electrical and Electronic Engineering, 2023)
Nowadays, Malaysia and the world have been facing increasing drowning cases in the pool, rivers, and even the beach. Drowning cases are the world’s third leading cause of accidental accident death and account for seven percent of all death related to the incidents, based to the World Health Organization (WHO). Drowning accidents are estimated at 320 000 deaths worldwide. Basically, drowning happens usually silently and only a few drowning people can wave or scream for help. There are many efforts to stop drowning cases, such as teaching diving, giving advice about how to prevent drowning, and making a protective drowning bracelet. Therefore, a project has been proposed to support swimmer tracking with bracelet sensors. This project is about a bracelet development to detect the user immediately in case of drowning. The bracelet can also detect a missing victim’s body location while it is drowning. The outcome of this project is to enable a person to gain extra protection while he or she is in an outdoor place such as a river, or beach. Last but foremost, this early-stage drowning detection device bracelet will hopefully help to minimize the incident of drowning in a lake, river, or sea.